European social integration: From convergence of countries to transnational relations between peoples - Jan Delhey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
European countries are becoming increasingly politically integrated and the process of integration has accelerated in recent years. But how much social integration is there within the Community? This article supplies a definition of European social integration, and thereby lays down the foundations necessary for answering this important sociological question. Instead of analysing the EU as a political system, I view the EU as a social space of non-state actors of different nationality, and concentrate on the intergroup relations between the national collectivities involved in the amalgamation process. I define social integration as being transnational and macro-social; my definition has a quantitative dimension (relating to mutual relevance) as well as a qualitative dimension (relating to cohesion). I will argue that this definition is more useful than the European Commission's approach, which equates social integration with the convergence of living and working conditions, and also more useful than the social policy approach, which equates social integration with the convergence of regulations and social policies. – – Unter dem Dach der Europäischen Union (EU) und ihrer Vorläufer ist die politische Integration Europas ein gutes Stück vorangekommen. Doch wie steht es mit der sozialen Integration innerhalb der Gemeinschaft? In diesem Artikel wird eine Definition von europäischer Sozialintegration vorgestellt, die uns erst in die Lage versetzt, diese soziologische Frage zu beantworten. Die EU wird dabei nicht als politisches System betrachtet, sondern als Sozialraum, bestehend aus den europäischen Nationen. Die Integration dieses Sozialraumes bestimmt sich durch die Quantität (diesen Aspekt nenne ich gegenseitige Relevanz) und Qualität (diesen Aspekt nenne ich sozialen Zusammenhalt) der Beziehungen zwischen den EU-Völkern. Meine Definition von europäischer Sozialintegration ist demnach transnational und makro-sozial. Es wird argumentiert, dass dieses Konzept brauchbarer ist als bestehende Ansätze wie der der Europäischen Kommission, bei dem möglichst einheitliche Arbeits- und Lebensbedingungen im Vordergrund stehen, und dem sozialpolitischen Ansatz, bei dem Integration mit der Vereinheitlichung von Sozialpolitik gleichgesetzt wird.
Keywords: 300; European Union; social integration; social cohesion; convergence; identity; transnational relations; Europäische Union; soziale Integration; sozialer Zusammenhalt; Konvergenz; Identität; transnationale Beziehungen.; EU-Sozialpolitik; Soziale Integration; EU-Staaten